2020
DOI: 10.1159/000509954
|View full text |Cite
|
Sign up to set email alerts
|

New Technologies in Clinical Trials in Corneal Diseases and Limbal Stem Cell Deficiency: Review from the European Vision Institute Special Interest Focus Group Meeting

Abstract: To discuss and evaluate new technologies for a better diagnosis of corneal diseases and limbal stem cell deficiency, the outcomes of a consensus process within the European Vision Institute (and of a workshop at the University of Cologne) are outlined. Various technologies are presented and analyzed for their potential clinical use also in defining new end points in clinical trials. The disease areas which are discussed comprise dry eye and ocular surface inflammation, imaging, and corneal neovascularization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 203 publications
(190 reference statements)
0
8
0
2
Order By: Relevance
“…11 A more extensive review of these practices and outcomes can be found in a recent report from the European Vision Institute. 37…”
Section: Limbal Stem Cell Transplantationmentioning
confidence: 99%
“…11 A more extensive review of these practices and outcomes can be found in a recent report from the European Vision Institute. 37…”
Section: Limbal Stem Cell Transplantationmentioning
confidence: 99%
“…In the light of this situation, we strived to develop and validate a GMP-compliant manufacturing process, by which ABCB5 + LSCs from cadaveric human limbal tissue can be expanded in vitro, isolated as a homogenous cell population and manufactured as a clinical-grade ATMP (Fig. 1) [45].…”
Section: Discussionmentioning
confidence: 99%
“…59 Recently, limbal stem cells from cadaver tissues have been isolated exclusively based on the positive expression of ABCB5, expanded in vitro as advanced therapy medicinal product (ATMP), and transplanted in clinical trials in patients with LSCD. 60 Autologous limbal cultures were the first stem cell-based therapy approved by ATMPs (in 2015), and it has also received marketing authorization as Holoclar from the European Medicine Agency. Holoclar uses the patient's own (autologous) limbal stem cells to treat unilateral LSCD.…”
Section: Historical Perspective and Progressive Shift In Limbal Stem Cell Transplantationmentioning
confidence: 99%
“… 59 Recently, limbal stem cells from cadaver tissues have been isolated exclusively based on the positive expression of ABCB5, expanded in vitro as advanced therapy medicinal product (ATMP), and transplanted in clinical trials in patients with LSCD. 60 …”
Section: Historical Perspective and Progressive Shift In Limbal Stem Cell Transplantationmentioning
confidence: 99%